(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2023)
Introduction: Differentiated thyroid carcinoma (DTC) are neoplasms derived from follicular cells, representing more than 90.6% of thyroid neoplasms. Thyroid puncture cytology is a procedure for diagnosis and treatment decision; however, little information in known in relation to the initial response to treatment. Objective: To demonstrate the relationship between thyroid fine needle aspiration cytology and the response to treatment in differentiated thyroid cancer. Methodology: this is a descriptive, relational, non-experimental cross-sectional study; with DTC patients from the Guayaquil Specialty Hospital “Dr. Abel Gilbert Ponton” in 2018 and 2019. Results: 163 patients were evaluated, the most frequent age group was 40 to 49 years (28.8%), women reached 91.4%, the Bethesda VI category a 52.8%, papillary carcinoma 95.1%; the intermediate recurrence risk 41.1%, and the excellent response 46.6%. When comparing the risk of recurrence and the response to treatment, the low risk had an excellent response in 58.5%, and the high risk had an incomplete structural response in 45.2%. Furthermore, when associating the Bethesda II category with an excellent response, this association was present in 88.2%, with statistical significance. Conclusion: Thyroid is related to the initial response to treatment, where Bethesda II is directly associated with an excellent response, with high intensity and a moderate level of prediction.